Pelatihan Pembuatan Permen Jelly Pepaya (Carica papaya) Bagi Ibu-Ibu Anggota PW Jemaat GKI Getsemani Kotaraja - Keiluhu, Henderina J.; Wambrauw, Daniel Z. K.; Farmawaty, Farmawaty; Ngamelubun, Geraldinalia; Pallo, Aryanti S.; Alatubir, Rosalinda (LPPM Uncen, 2025)
Buah pepaya merupakan buah tropis yang mudah diperoleh, memiliki banyak manfaat kesehatan dan dapat dikonsumsi dalam bentuk buah segar, buah potong atau sayur Papaya is a tropical fruit that is easy to obtain, has many health benefits, and can be consumed in the form of fresh-cut fruit, or vegetables, as well as processed products. Papaya fruit can be a basic ingredient for making papaya jelly candy. This community service activity was carried out as a form of dissemination about the benefits of papaya fruit and training in making papaya jelly candy so that it can be an entrepreneurial opportunity other than for personal consumption. Material about making papaya jelly candy was delivered using a lecture method followed by the practice of making papaya jelly. This activity was held on August 24 2024 and was attended by 26 members of the Women's Association of the Indonesian Christian Church Getsemani Kotaraja Jayapura as participants. The papaya jelly candy produced is a healthy product because it does not use additional ingredients such as food coloring. This activity went well and the participants participated very enthusiastically. Participants felt the benefits of the activity directly as evidenced by the testimonials submitted by two participants representing the mothers of PW GKI Getsemani Kotaraja. The results of the activity evaluation showed positive participant responses with a satisfaction level percentage of 34% of participants strongly agreeing and 64% of participants agreeing.